High-strength aluminum alloy, processing method and application
By optimizing the composition of Al-Mg-Si alloy and using rolling + rolling + laser welding, the problem of difficult to develop high-strength and good formability in the existing technology is solved, and high-strength aluminum alloy products with high tensile strength, yield strength and elongation are achieved, which are suitable for high-strength structural parts.
Patent Information
- Application Number
- CN202510087158.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult to develop high-strength 6-series aluminum alloys with tensile strength between 450-510MPa and yield strength between 415-470MPa, and both have good extrusion efficiency and processing forming properties.
Based on Al-Mg-Si alloy, through the optimization design of alloy elements and the processing method of rolling + rolling + laser welding, a high-strength aluminum alloy with tensile strength 450-510MPa, yield strength 415-470MPa and elongation ≥10%.
It achieves high strength and good processing and forming properties, and is suitable for high-strength structural parts of automobiles and rail transit, especially automobile anti-collision beams.
Smart Images

Figure CN119843121A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength aluminum alloy, a processing method and application, and belongs to the technical field of metal material processing. Background Art
[0002] As an important material for lightweighting automobiles and rail transit, aluminum alloys have put forward higher and higher requirements for their performance with the development of the industry. They must not only have high strength, but also have good processing and forming properties, such as good bending and welding properties. At present, lightweight structural parts, such as automobile anti-collision beams, are commonly made of 6082 aluminum alloy, which is usually formed by extrusion processing, and its yield strength is less than 300MPa; the patent "CN118086732A Aluminum Profile and Its Preparation Method and Application" has optimized the design of the components, added precious rare earth elements, and adopted the extrusion processing method. The yield strength of the 6-series high-strength aluminum alloy it developed can only reach 360MPa. For conventional 6-series aluminum alloys and 6-series high-strength aluminum alloys with added rare earth elements, it is difficult to reach a yield strength of 400MPa by extrusion processing.
[0003] The patent "CN 117867342 B A QP-II-based aluminum alloy strengthening phase and its preparation method and application" designed a new composition. Through the new strengthening phase mechanism, a high-strength aluminum alloy with a yield strength exceeding 470MPa was obtained. If this type of high-strength 6 series aluminum alloy is used in profiles with cavity structures, there are shortcomings, low extrusion efficiency, general extrusion speed less than 0.8mm / s, and high extrusion cost.
[0004] The existing extrusion technology has a large technical bottleneck in developing a yield strength of 415-470MPa while having good extrusion efficiency and good processing formability. Therefore, it is urgent to develop a new type of high-strength 6 series aluminum alloy to meet the performance requirements of such products.
[0005] The present invention is based on Al-Mg-Si alloy, optimizes the design of alloy elements, and breaks away from the traditional extrusion processing method. It introduces roll pressing and laser welding, that is, adopts the processing method of rolling + roll pressing + laser welding, and successfully develops aluminum alloy products with a tensile strength of 450-510MPa, a yield strength of 415-470MPa, an elongation of ≥10%, and good roll bending and welding formability. The aluminum alloy products can be widely used in high-strength structural materials for automobiles and rail transportation, and commonly used products are automobile anti-collision beams. Summary of the invention
[0006] The purpose of the present invention is to solve the technical bottleneck of the existing extrusion technology, which is difficult to develop a high-strength aluminum alloy with a tensile strength of 450-510MPa, a yield strength of 415-470MPa, good extrusion efficiency, and good processing formability, and to provide a high-strength aluminum alloy.
[0007] At the same time, the present invention provides a processing method using a high-strength aluminum alloy.
[0008] At the same time, the present invention provides an application of a high-strength aluminum alloy in an automobile anti-collision beam.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0010] A high-strength aluminum alloy comprises the following components: Mg 1.0-1.5wt.%, Si 0.85-1.5wt.%, Cu 0.6-1.4wt.%, Mn 0.4-1.2wt.%, Cr 0.10-0.30wt.%, Ti 0.01-0.03wt.%, Zn 0.10-0.30wt.%, Fe≤0.2wt.%, and the balance is Al and inevitable impurities.
[0011] A processing method of high-strength aluminum alloy is as follows:
[0012] S1. According to the mass percentage of each element in the aluminum alloy composition, the raw materials are weighed for melting and casting. A semi-continuous casting method is adopted, with a melting temperature of 710-770°C, a casting temperature of 690-730°C, and a casting speed of 30-120mm / min to cast into a flat ingot of the required size. The cross-sectional dimensions of the flat ingot are: thickness 200-500mm, width 500-1600mm.
[0013] S2. The flat ingot is homogenized;
[0014] S3. The homogenized ingot is preheated, hot rolled, cold rolled, and rolled to the target thickness;
[0015] S4. The cold rolled material is subjected to solution quenching treatment in an air cushion furnace;
[0016] S5. After aging treatment, the plate is obtained;
[0017] S6. The plate is rolled and laser welded to finally obtain the product with the required cross-section.
[0018] Furthermore, the high-strength aluminum alloy material, preferably the alloy formula raw material includes the following components: Mg 1.1-1.4wt.%, Si 0.9-1.4wt.%, Cu 0.65-1.3wt.%, Mn 0.5-1.0wt.%, Cr 0.15-0.25wt.%, Ti 0.015-0.025wt.%, Zn 0.15-0.25wt.%, Fe≤0.18wt.%, and the balance is Al and unavoidable impurities.
[0019] Furthermore, in S2, the homogenization treatment process is: from room temperature, the temperature is increased at a rate of 20℃-70℃ / h to 400℃-460℃, and kept warm for 4h-8h; then the temperature is increased at a rate of 40℃-90℃ / h to 530℃-580℃, and kept warm for 8h-20h, and water-cooled after being taken out of the furnace.
[0020] Furthermore, in S3, the slab is preheated before hot rolling, and the preheating process is: from room temperature, the temperature is increased at a rate of 50°C-100°C / h to 460°C-520°C, and the temperature is kept for 4h-12h.
[0021] Furthermore, in S3, the slab is hot rolled to 5 mm-12 mm and cold rolled to 0.5 mm-3.5 mm.
[0022] Furthermore, the hot rolling temperature is 460-520°C, the hot rolling end temperature is 250-380°C, the hot rolled coil is air-cooled to room temperature, and then cold-rolled.
[0023] Furthermore, in S4, the air cushion furnace solution process is: keeping at 550°C-570°C for 0.2-1.5h and water cooling.
[0024] Furthermore, in S5, the aging treatment process is a double-stage aging treatment, with the first stage temperature being 100°C-150°C and the insulation time being 1-4h; the second stage temperature being 170°C-190°C and the insulation time being 6h-15h.
[0025] Further, in S6, the plate after aging has a first side and a second side opposite to each other in the width direction, the first side of the plate is rolled to form a first tube, and the opening of the first tube is laser welded so that the first tube has a closed cross section. The side of the plate having the first tube and the second side of the plate are rolled to form a second tube, and the opening of the second tube is laser welded so that the second tube has a closed cross section, the second tube has an inner cavity, and the first tube is located in the inner cavity of the second tube, thereby forming a profile.
[0026] Further, in S6, the laser welding process is: laser power 1200-2000W, welding speed 5-35mm / s, pulse frequency 25-35HZ, duty cycle 50-70%.
[0027] Furthermore, the high-strength aluminum alloy product has obtained a QP-Ⅱ-based strengthening phase structure with excellent comprehensive performance, tensile strength of 450-510MPa, yield strength of 415-470MPa, elongation ≥10%, and good roll bending and welding formability. It can be used in high-strength structural materials for automobiles and rail transit, and a commonly used product is automobile anti-collision beams.
[0028] An automobile anti-collision beam profile comprises a first tube and a second tube, wherein the first tube is located in an inner cavity of the second tube, and both the first tube and the second tube have closed cross-sections; the profile is prepared from a high-strength aluminum alloy of the present invention.
[0029] In the present invention, an aluminum alloy product with QP-II as the main strengthening phase and a preparation method thereof are obtained by designing the alloy composition and controlling the processing method. The main strengthening phase obtained in the prior art "CN 117867342 B A QP-II-main strengthening phase aluminum alloy and its preparation method and application" is the same, both of which are QP-II phases. The differences are: the design ranges of the elements Mg, Si, Cu, Mn, and Cr are different, and the alloy of the present invention adds the elements Ti and Zn, and limits the content of the element Fe; jump out of the traditional extrusion or rolling forming method, and adopt a new processing method combination, namely: rolling + roller pressing + laser welding processing method to prepare a high-strength aluminum alloy product.
[0030] The present invention has the following beneficial effects:
[0031] The present invention controls the content of the main alloy elements Mg, Si, and Cu, and adds microalloying elements such as Mn and Cr, invents and designs new alloy components, and prepares an aluminum alloy with QP-Ⅱ as the main strengthening phase through heat treatment and processing technology control; matches the alloy components, adopts a new processing method combination, that is, rolling + roller pressing + welding forming method, and develops a high-strength 6 series aluminum alloy with a tensile strength of 450-510MPa, a yield strength of 415-470MPa, an elongation of ≥10%, and good roll bending and welding formability. It can be widely used in high-strength structural materials for automobiles and rail transportation.
[0032] The invention discloses a high-strength aluminum alloy material, which comprises the following components by mass percentage: Mg 1.0-1.5wt.%, Si 0.85-1.5wt.%, Cu 0.6-1.4wt.%, Mn 0.4-1.2wt.%, Cr 0.10-0.30wt.%, Ti 0.01-0.03wt.%, Zn 0.10-0.30wt.%, Fe≤0.2wt.%, and the remainder is Al and inevitable impurities. The material processing method is as follows: firstly, the raw materials are weighed and smelted according to the mass percentage of each element in the aluminum alloy composition, and large-size flat ingots are made through semi-continuous casting, the flat ingots are homogenized, and then preheated, hot rolled, and cold rolled to the target thickness, the cold rolled material is subjected to solid solution quenching treatment in an air cushion furnace, and then subjected to aging treatment to obtain a plate, the plate is subjected to rolling and laser welding, and finally a product with a desired cross section is obtained. The high-strength aluminum alloy product prepared by the present invention has excellent comprehensive properties, a tensile strength of 450-510 MPa, a yield strength of 415-470 MPa, and an elongation of ≥10%, and can be applied to high-strength structural parts of automobiles and rail transportation. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a schematic structural diagram of a profile in an embodiment of the present invention;
[0034] Figure 2 The microstructure of Example 1 of the present invention after solution aging in an air cushion furnace, wherein (a) EBSD grain map, (b) TEM bright field image;
[0035] Figure 3 This is the microstructure of comparative example 5 of the present invention after solution aging in an air cushion furnace, wherein (a) EBSD grain map, (b) TEM bright field image;
[0036] The figure numbers of the above drawings are: 1, first tube; 11, first tube welding position; 2, second tube; 21, inner cavity; 22, second tube welding position. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1.
[0040] The product is prepared by the following method:
[0041] 1) Raw materials are weighed according to the mass percentage of each element in the aluminum alloy composition for melting and casting. A semi-continuous casting method is adopted with a melting temperature of 750° C., a casting temperature of 700° C., and a casting speed of 80 mm / min to cast a flat ingot of the required size. The cross-sectional dimensions of the flat ingot are: thickness 400 mm, width 1300 mm.
[0042] 2) The flat ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 440°C at a heating rate of 50°C / h and kept at this temperature for 5 hours, and then the temperature is increased to 570°C at a heating rate of 60°C / h and kept at this temperature for 12 hours. After homogenization, the flat ingot is subjected to water cooling treatment.
[0043] 3) The slab is preheated from room temperature to 490°C at a rate of 80°C / h and kept at this temperature for 6 hours.
[0044] 4) The preheated ingot is hot rolled to 6 mm, and the billet is cold rolled to 2 mm.
[0045] 5) The cold rolled material is solution quenched in an air cushion furnace, kept at 560°C for 0.5h, and quenched.
[0046] 6) Then carry out aging treatment, the aging treatment process is a double-stage aging treatment, the first stage temperature is 120°C, the insulation time is 3h; the second stage temperature is 180°C, the insulation time is 9h.
[0047] 7) The first side of the plate in the width direction after aging is rolled to form a first tube 1, and the opening 11 of the first tube 1 (i.e., the first tube welding position 11) is laser welded, and the process parameters are: laser power 1700W, welding speed 20mm / s, pulse frequency 30HZ, duty cycle 60%, so that the first tube 1 has a closed cross-section. One side of the first tube 1 and the second side of the plate are rolled to form a second tube 2, and the opening 22 of the second tube (i.e., the second tube welding position 22) is laser welded, and the process parameters are: laser power 1700W, welding speed 20mm / s, pulse frequency 30HZ, duty cycle 60%, so that the second tube 2 has a closed cross-section, and the second tube 2 has an inner cavity 21, and the first tube 1 is located in the inner cavity 21 of the second tube 2, thereby forming a profile, and the profile is an anti-collision beam product, specifically as Figure 1 shown.
[0048] In Example 1, the contents of the main alloying elements Mg, Si, and Cu are controlled within a certain range, and microalloying elements Mn and Cr are added. By optimizing the design of alloy composition, controlling the heat treatment system and processing technology, an excellent microstructure is obtained, such as Figure 2 As shown, the strengthening precipitate phase is evenly dispersed Figure 2 (b) At the same time, a fine recrystallized structure was obtained Figure 2(a), the maximum grain size is less than 100μm, and the prepared product has excellent comprehensive properties: the tensile strength can reach 460MPa, the yield strength can reach 420MPa, the elongation can reach 11.5%, and it also has good rolling and welding properties.
[0049] A high-strength aluminum alloy in this embodiment is used in high-strength structural materials for automobiles and rail transit, and the high-strength structural materials include automobile anti-collision beams.
[0050] An automobile anti-collision beam profile, the profile comprises a first tube 1 and a second tube 2, the first tube 1 is located in an inner cavity 21 of the second tube 2, and the first tube 1 and the second tube 2 both have closed cross-sections; the profile is prepared from a high-strength aluminum alloy of this embodiment.
[0051] Example 2-Example 3
[0052] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1.
[0053] The processing and preparation methods of Example 2-Example 3 are the same as those of Example 1, except that the content of the main alloy elements is controlled differently; the content of the main alloy elements Mg, Si, and Cu in Example 2 is controlled at the lower limit of the present invention, and the content of the main alloy elements Mg, Si, and Cu in Example 3 is controlled at the upper limit of the present invention, which can effectively ensure the strength of the alloy. Example 2 can make the product tensile strength reach 453MPa, the yield strength reach 416MPa, and the elongation reach 12.0%. Example 3 can make the product tensile strength reach 505MPa, the yield strength reach 465MPa, and the elongation reach 10.5%
[0054] Example 4-Example 5
[0055] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1.
[0056] The raw material chemical composition of Example 4-Example 5 is the same as that of Example 1, except that the solution holding time of the cold rolled material in the air cushion furnace is different, the holding time of Example 4 is controlled at 12 minutes, and the holding time of Example 5 is controlled at 1.5 hours. In order to ensure the solution effect of the alloy of the present invention, the shortest holding time is not less than 12 minutes; in order to prevent the coarsening of grains during the solution process, the longest holding time does not exceed 1.5 hours.
[0057] Example 6
[0058] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1.
[0059] The product is prepared by the following method:
[0060] 1) Raw materials are weighed according to the mass percentage of each element in the aluminum alloy composition for melting and casting. A semi-continuous casting method is adopted with a melting temperature of 710° C., a casting temperature of 690° C., and a casting speed of 120 mm / min to cast a flat ingot of the required size. The cross-sectional dimensions of the flat ingot are: thickness 200 mm, width 500 mm.
[0061] 2) The flat ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 400°C at a heating rate of 20°C / h and kept at this temperature for 4 hours, and then the temperature is increased to 530°C at a heating rate of 40°C / h and kept at this temperature for 8 hours. After homogenization, the flat ingot is subjected to water cooling treatment.
[0062] 3) The slab is preheated from room temperature to 460°C at a rate of 50°C / h and kept at this temperature for 4h.
[0063] 4) The preheated ingot is hot rolled to 5 mm, and the billet is cold rolled to 0.5 mm.
[0064] 5) The cold rolled material is solution quenched in an air cushion furnace, kept at 550°C for 0.5h, and quenched.
[0065] 6) Then carry out aging treatment, the aging treatment process is a double-stage aging treatment, the first stage temperature is 100°C, the insulation time is 1h; the second stage temperature is 170°C, and the insulation time is 6h.
[0066] 7) The first side of the plate in the width direction after aging is rolled to form a first tube 1, and the opening 11 of the first tube 1 (i.e., the first tube welding position 11) is laser welded, and the process parameters are: laser power 1200W, welding speed 5mm / s, pulse frequency 25HZ, duty cycle 50%, so that the first tube 1 has a closed cross section. One side of the first tube 1 and the second side of the plate are rolled to form a second tube 2, and the opening 22 of the second tube (i.e., the second tube welding position 22) is laser welded, and the process parameters are: laser power 1200W, welding speed 5mm / s, pulse frequency 25HZ, duty cycle 50%, so that the second tube 2 has a closed cross section, and the second tube 2 has an inner cavity 21, and the first tube 1 is located in the inner cavity 21 of the second tube 2, thereby forming a profile, which is an anti-collision beam product.
[0067] A high-strength aluminum alloy in this embodiment is used in high-strength structural materials for automobiles and rail transit, and the high-strength structural materials include automobile anti-collision beams.
[0068] An automobile anti-collision beam profile, the profile comprises a first tube 1 and a second tube 2, the first tube 1 is located in an inner cavity 21 of the second tube 2, and the first tube 1 and the second tube 2 both have closed cross-sections; the profile is prepared from a high-strength aluminum alloy of this embodiment.
[0069] Example 7
[0070] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1.
[0071] The product is prepared by the following method:
[0072] 1) Raw materials are weighed according to the mass percentage of each element in the aluminum alloy composition for melting and casting. A semi-continuous casting method is adopted with a melting temperature of 770° C., a casting temperature of 730° C., and a casting speed of 30 mm / min to cast a flat ingot of the required size. The cross-sectional dimensions of the flat ingot are: thickness 500 mm, width 1600 mm.
[0073] 2) The flat ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 460°C at a heating rate of 70°C / h and kept at this temperature for 8 hours, and then the temperature is increased to 580°C at a heating rate of 90°C / h and kept at this temperature for 20 hours. After homogenization, the flat ingot is subjected to water cooling treatment.
[0074] 3) The slab is preheated from room temperature to 520°C at 100°C / h and kept at this temperature for 12h.
[0075] 4) The preheated ingot is hot rolled to 12 mm, and the billet is cold rolled to 3.5 mm.
[0076] 5) The cold rolled material is solution quenched in an air cushion furnace, kept at 570°C for 0.5h, and quenched.
[0077] 6) Then carry out aging treatment, the aging treatment process is a double-stage aging treatment, the first stage temperature is 150°C, the insulation time is 4h; the second stage temperature is 190°C, the insulation time is 15h.
[0078] 7) The first side of the plate in the width direction after aging is rolled to form a first tube 1, and the opening 11 of the first tube 1 (i.e., the first tube welding position 11) is laser welded, and the process parameters are: laser power 2000W, welding speed 35mm / s, pulse frequency 35HZ, duty cycle 70%, so that the first tube 1 has a closed cross section. One side of the first tube 1 and the second side of the plate are rolled to form a second tube 2, and the opening 22 of the second tube (i.e., the second tube welding position 22) is laser welded, and the process parameters are: laser power 2000W, welding speed 35mm / s, pulse frequency 35HZ, duty cycle 70%, so that the second tube 2 has a closed cross section, and the second tube 2 has an inner cavity 21, and the first tube 1 is located in the inner cavity 21 of the second tube 2, thereby forming a profile, and the profile is an anti-collision beam product.
[0079] A high-strength aluminum alloy in this embodiment is used in high-strength structural materials for automobiles and rail transit, and the high-strength structural materials include automobile anti-collision beams.
[0080] An automobile anti-collision beam profile, the profile comprises a first tube 1 and a second tube 2, the first tube 1 is located in an inner cavity 21 of the second tube 2, and the first tube 1 and the second tube 2 both have closed cross-sections; the profile is prepared from a high-strength aluminum alloy of this embodiment.
[0081] Example 8
[0082] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1. The processing method is the same as that of Embodiment 1.
[0083] Example 9
[0084] The raw material composition of the high-strength aluminum alloy material provided in this embodiment is shown in Table 1. The processing method is the same as that of Embodiment 1.
[0085] Comparative Example 1
[0086] The raw material composition of the aluminum alloy material provided in this comparative example is shown in Table 1.
[0087] The product is prepared by the following method:
[0088] 1) Raw materials were weighed and smelted according to the mass percentage of each element in the aluminum alloy composition (the same composition and content as in Example 1), and semi-continuously cast into ingots with a size of Φ228 mm.
[0089] 2) The round ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 440°C at a heating rate of 50°C / h and kept at this temperature for 5 hours, and then the temperature is increased to 570°C at a heating rate of 60°C / h and kept at this temperature for 12 hours, and then water-cooled after homogenization.
[0090] 3) The round ingot is extruded, the aluminum bar temperature is 500°C, the extrusion speed is 0.7 mm / s, the profile outlet temperature is 520°C, and the profile is cooled by 100% strong wind.
[0091] 4) The profile is subjected to aging treatment, and the aging treatment process is a double-stage aging treatment, the first stage temperature is 120°C, the insulation time is 3h; the second stage temperature is 180°C, the insulation time is 9h.
[0092] 5) After aging, the profile is finally obtained, and the profile is an anti-collision beam product.
[0093] The chemical composition of the materials used in this comparative example is the same as that in Example 1, but the processing and preparation methods are very different. This comparative example adopts the conventional extrusion processing method. In the process of extruding the profile of the cavity structure, in order to ensure the cross-sectional dimensions and shape and position tolerances of the profile, air cooling is usually adopted. At this time, it is difficult to exert the best solid solution strengthening effect of the material; but if spraying or water cooling is adopted, it is beneficial to improve the strength of the material, but it is difficult to ensure the cross-sectional dimensions and shape and position tolerances. In order to ensure the cross-sectional dimensions and shape and position tolerances of the product, this comparative example adopts strong wind cooling. After aging, the tensile strength of the profile is 423MPa, the yield strength is 401MPa, and the elongation is 10.1%, which does not achieve the best mechanical properties of the material.
[0094] Comparative Example 2-Comparative Example 3
[0095] The raw material composition of the aluminum alloy material provided in this comparative example is shown in Table 1.
[0096] Comparative Example 2-Comparative Example 3 is processed and prepared in the same manner as Example 1, except that the contents of the main alloy elements Mg, Si, and Cu are different. The addition amount of alloy elements Mg, Si, and Cu in Comparative Example 2 is relatively low, while the addition amount of alloy elements Mg, Si, and Cu in Comparative Example 3 is relatively high. The Mg content of Comparative Example 2 is 0.95wt.%, the Si content is 0.80wt.%, and the Cu content is 0.55wt.%. After the alloy is processed, the tensile strength of the product is 419MPa, the yield strength is 397MPa, and the elongation is 13.0%, which does not meet the target requirements.
[0097] In comparative example 3, the Mg content is 1.55wt.%, the Si content is 1.55wt.%, and the Cu content is 1.45wt.%. After processing, the product has a tensile strength of 515MPa, a yield strength of 475MPa, and an elongation of 7.9%. The strength of the alloy is high, but the elongation is lower than 8%, and the comprehensive performance does not meet the target requirements. At the same time, after the alloy elements are increased, not only the cost of the material increases, but also the roll forming property and welding performance become relatively poor.
[0098] Comparative Example 4
[0099] The raw material composition of the aluminum alloy material provided in this comparative example is shown in Table 1.
[0100] The chemical composition of the raw materials in this comparative example is the same as that in Example 1, except that the solution quenching process of the cold rolled material in the air cushion furnace is 560°C for 10 minutes. In this comparative example, the cold rolled material has a short insulation time of only 10 minutes, which cannot achieve the best solution effect of the material. After aging, the material has a tensile strength of 430MPa, a yield strength of 403MPa, and an elongation of 11.4%.
[0101] Comparative Example 5
[0102] The raw material composition of the aluminum alloy material provided in this comparative example is shown in Table 1. The raw material chemical composition of this comparative example is the same as that of Example 1, except that the solution quenching process of the cold-rolled material in the air cushion furnace is 560°C for 2.0h. In this comparative example, the cold-rolled material insulation time is extended, such as Figure 3 As shown, the strengthening precipitate phase is evenly dispersed Figure 3 (b), but the grains have undergone a certain degree of coarsening, e.g. Figure 3 (a), the maximum grain size exceeds 150 μm, the comprehensive mechanical properties are reduced, the material tensile strength is 433 MPa, the yield strength is 404 MPa, and the elongation is 11.2%.
[0103] Table 1 Composition of various alloy raw materials corresponding to Examples 1 to 9 and Comparative Examples 1 to 5 (by mass percentage)
[0104]
[0105] The aluminum alloy products of Examples 1 to 9 and Comparative Examples 1 to 5 were subjected to mechanical property tests according to GB / T 16865-2013 standard. The results are shown in Table 2.
[0106] Table 2 Test results of the corresponding products of Examples 1 to 9 and Comparative Examples 1 to 5
[0107]
[0108] In Table 2, - represents that comparative example 1 adopts conventional extrusion processing method to directly extrude profiles without rolling and welding.
[0109] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0110] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength aluminum alloy, characterized in that: The invention comprises the following components: Mg 1.0-1.5wt.%, Si 0.85-1.5wt.%, Cu 0.6-1.4wt.%, Mn 0.4-1.2wt.%, Cr 0.10-0.30wt.%, Ti 0.01-0.03wt.%, Zn 0.10-0.30wt.%, Fe≤0.2wt.%, and the balance is Al and inevitable impurities.
2. A high-strength aluminum alloy according to claim 1, characterized in that: The invention comprises the following components: Mg 1.1-1.4wt.%, Si 0.9-1.4wt.%, Cu 0.65-1.3wt.%, Mn 0.5-1.0wt.%, Cr0.15-0.25wt.%, Ti0.015-0.025wt.%, Zn 0.15-0.25wt.%, Fe≤0.18wt.%, and the balance is Al and inevitable impurities.
3. The high-strength aluminum alloy according to claim 1, characterized in that: Tensile strength 450-510MPa, yield strength 415-470MPa, elongation ≥10%, with roll bending and welding formability.
4. A method for processing a high-strength aluminum alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, weighing raw materials according to the mass percentage of each element in the aluminum alloy composition, melting and casting, and obtaining a flat ingot; S2, the slab is homogenized; the homogenization process is: from room temperature, the heating rate is 20℃-70℃ / h, the temperature is increased to 400℃-460℃, and the temperature is kept for 4h-8h; then the temperature is increased to 530℃-580℃ at a heating rate of 40℃-90℃ / h, and the temperature is kept for 8h-20h, and the slab is water-cooled after being taken out of the furnace; S3, the slab after homogenization treatment is preheated, hot rolled, and cold rolled to the target thickness; the slab is preheated before hot rolling, and the preheating process is: from room temperature, the heating rate is 50℃-100℃ / h to 460℃-520℃, and the temperature is kept for 4h-12h; the slab is hot rolled to 5mm-12mm; cold rolled to 0.5mm-3.5mm; and the cold rolled material is obtained; S4, the cold rolled material is subjected to solution quenching treatment in an air cushion furnace; the air cushion furnace solution process is: keeping at 550℃-570℃ for 0.2-1.5h, water cooling; S5, and then undergo aging treatment to obtain the plate; the aging treatment process is a double-stage aging treatment, the first stage temperature is 100℃-150℃, the insulation time is 1-4h; the second stage temperature is 170℃-190℃, the insulation time is 6h-15h; S6, the plate is rolled and laser welded to finally obtain a product with the required cross-section.
5. The processing method according to claim 4, characterized in that: In S1, the smelting and casting adopts a semi-continuous casting method, with a melting temperature of 710-770°C, a casting temperature of 690-730°C, and a casting speed of 30-120mm / min, and is cast into a slab of required size. The cross-sectional dimensions of the slab are: thickness 200-500mm, width 500-1600mm.
6. The processing method according to claim 4, characterized in that: In S3, the hot rolling temperature is 460-520°C, the hot rolling end temperature is 250-380°C, the hot rolled coil is air-cooled to room temperature, and then cold rolled.
7. The processing method according to claim 4, characterized in that: In S6, the plate after aging has a first side and a second side opposite to each other in the width direction, the first side of the plate is rolled to form a first tube, and the opening of the first tube is laser welded so that the first tube has a closed cross-section; the side of the plate having the first tube and the second side of the plate are rolled to form a second tube, and the opening of the second tube is laser welded so that the second tube has a closed cross-section, the second tube has an inner cavity, and the first tube is located in the inner cavity of the second tube, thereby forming a profile, that is, a product with a required cross-section.
8. The processing method according to claim 7, characterized in that: The laser welding process is: laser power 1200-2000W, welding speed 5-35mm / s, pulse frequency 25-35HZ, duty cycle 50-70%.
9. The high-strength aluminum alloy according to any one of claims 1 to 3 is used in high-strength structural materials for automobiles and rail transportation, characterized in that: High-strength structural materials include automotive anti-collision beams.
10. An automobile anti-collision beam profile, characterized in that: The high-strength aluminum alloy is prepared according to any one of claims 1 to 3.
Citation Information
Patent Citations
Aluminum alloy with QP-II as main strengthening phase and preparation method and application thereof
CN117867342B
Cited By
6-series high-strength aluminum alloy material capable of being rapidly extruded
CN122012996A